Expansion of Liver Cancer Stem Cells During Aging in Methionine Adenosyltransferase 1A–Deficient Mice - Bart Rountree, C. (2008)
Methionine adenosyltransferase (MAT) is an essential enzyme that catalyzes the biosynthesis of S-adenosylmethionine. Hepatic MAT activity falls in chronic liver diseases, and mice lacking Mat1a are predisposed to liver injury and develop hepatocellular carcinoma (HCC) spontaneously by 18 months. The current work examined the hypothesis that liver cancer stem cells contribute to HCC in this model. Livers from 6- and 18-month-old Mat1a-knockout (KO) mice and their wild-type (WT) littermates were fractionated and isolated by flow cytometry. CD45− nonparenchymal (NP) cells were cultured using liver stem cell conditions. Cells were analyzed by real-time PCR and fluorescent immunohistochemistry (FIHC). Tumor formation was assessed by injecting 1 × 10(6) CD133+CD49f+ cells intraperitoneally into immune-deficient mice. The proportion of CD49f+ and CD133+ cells in the CD45-NP fraction increased 4.5- to 5.5-fold from 6 to 18 months in KO mice but not in their WT littermates. Compared to CD49f− cells from old KO mice, CD49f+ cells from the same animals had a markedly increased expression of several oncogenes. CD133+ cells with CD49f coexpression were selected in vitro and exhibited rapid growth, with the expression of biliary cytokeratins, α-fetoprotein, and c-Met by FIHC. Clonal expansion of single CD133+CD49f+ cells revealed maintenance of bipotency. After CD133+CD49f+ cells were injected into immune-deficient mice, 3 of the 8 mice developed tumors of liver epithelial cells after 6–8 weeks. CONCLUSION: Matla(−/−) mice have expansion of liver stem cells as they age. These cells have increased expression of several oncogenes and are tumorigenic in vivo. This is the first demonstration of adult liver stem cells possessing tumorigenic potential without the use of a carcinogen or manipulation of tumor-suppressor or oncogene expression.